A PEDAGOGIA CULTURAL EM UM CANAL EDUCATIVO: Currículo Cultural nas aulas de Educação Física - SARAH DA SILVA CORRÊA LIMA (2025)
Physical Education in schools has a history strongly linked to the disciplining of the body. Its trajectory linked to the military and health context reinforces its identity construction as a curricular discipline linked to the care and indoctrination of the body-machine. Due to the pandemic period experienced between 2020 and 2022, it was necessary for schools to remodel their teaching practices for remote conditions. For this reason, the Municipal Department of Education of Campo Grande (SEMED) organized and made available video classes, which were broadcast on open television and, later, inserted into the digital platform YouTube. Thus, this research had as its general objective to investigate the cultural pedagogies produced in the cultural curriculum of the videos of the Physical Education discipline, available on the channel “TV REME Campo Grande”, and how power relations are established/tensioned through these artifacts, with the specific objectives of analyzing how the social markers of differences (gender; generation; social class, and; race) are presented in the videos analyzed; problematizing how power relations are established in them; in addition to observing how they form different subjects, with their subjectivities and identities, based on their curriculum. This research is guided by the genealogical perspective of power, a methodological operator idealized by the philosopher Michel Foucault. The genealogical method is not a traditional methodology with pre-established standards and steps that must be strictly followed, but rather different paths that the researcher can establish so that, through them, he or she can understand how subjects are formed, under the intersections of power relations, microphysical practices, power games and subjectivation. As can be seen, the pedagogies resulting from the videos are permeated by power relations, which are in tension with social markers of difference in race, gender, generation, social class, in addition to a specific cultural curriculum of power relations, as well as the pedagogical practices in the Physical Education discipline, corroborating the identity production that the curriculum found in it is one that disciplines the body, by effectively applying the methodological devices of disciplinary power and biopower. However, this cultural curriculum also facilitated the production of an agency in the social markers of race and gender, enabling other subjectivities that escape the pre-established norms.